ANALISIS RESIKO REAKTOR KIMIA BERDASARKAN STANDAR INSPEKSI BERBASIS RESIKO (RISK BASED INSPECTION: RBI) API 581 - Soelaiman, T. A Fauzi; Taufik, Ahmad; Soma, Tito Arya (Mesin, 2004)
Inspection is an activity to detect and evaluate the possibility of damage or degradation of operating equipment. Risk Based Inspection (RBI) Method is one of management inspection methods based on risk level of an equipment or a work unit. The RBI Method uses a combination of two parameters (category of failure possibility and category of failure consequence) for determining the level of risk for industrial equipment. The method was applied to several chemical reactors in a petrochemical industry such as Hydrotreater, Secondary Reformer, Shift Converter, Ammonia Synthesis Converter, Methanator, Zinc Oxide Guard, and Mercury Guard Chamber. Using qualitative RBI method, the risks of the equipment are as follow: Hydrotreater (Low Risk), Secondary Reformer (Low Risk), Shift Converter (Low Risk), Ammonia Synthesis Converter (Low Risk), Methanator (Low Risk), Zinc Oxide Guard (Low Risk), and Mercury Guard Chamber (Low Risk). Meanwhile, using semi-quantitative RBI method, the risks were found to be: Hydrotreater (High Risk), Secondary Reformer (High Risk), Shift Converter (High Risk), Ammonia Synthesis Converter (High Risk), Methanator (High Risk), Zinc Oxide Guard (High Risk), Mercury Guard Chamber (High Risk).